Domestic violence: intervention, prevention, policies and solutions - Davis, Richard L. (CRC Press, 2008)
Introduction -- Domestic violence and violent behavior in general -- Battered statistics harm all victims -- Dating abuse -- The California conundrum : keeping the promise -- Rape and sexual assault -- Mandatory domestic violence arrest policies -- The Colorado star chamber -- Ain't I a victim -- In memoriam -- Rethinking victimization -- Afterword